Newborn Safety Bundle to Prevent Falls and Promote Safe Sleep. Issue 1 (January 2018) - Lipke, Bethann; Gilbert, Gael; Shimer, Heather; Consenstein, Larry; Aris, Christine; Ponto, Lynne; Lafaver, Susan; Kowal, Christopher
Abstract: Purpose: At our Baby-Friendly USA hospital, with at least 80% of mothers breastfeeding and rooming-in, it is not uncommon for mothers to fall asleep in their hospital bed while feeding. The aim of this study was to develop a newborn infant safety bundle and evaluate its efficacy in helping reduce unsafe sleep situations while simultaneously preventing newborn falls. Study Design and Method: Data were collected in March 2015 using an infant at risk-to-fall instrument prior to nurses initiating the newborn infant safety bundle. The bundle included: (a) a parent safety agreement; (b) education, teach-back, and role modeling of safe sleep practices; and (c) implementation of a reporting and debriefing system for infant falls. All new mothers were eligible for inclusion. Data were collected over a random month every quarter for four quarters (through June 2016). Results: Fourteen percent ( n = 23) of babies born at the hospital in March 2015 were found to be exposed to risk-to-fall situations; over half of their mothers were found asleep and still holding the baby. Following bundle implementation, identified unsafe sleep situations during June 2015 to June 2016 have trended down with no reports of an infant fall through May 2017. Clinical Implications: Increasing parental awareness, understanding, and participation in safe sleep practice creates and maintains a safer infant environment in the hospital setting. Abstract : It is not uncommon for mothers to fall asleep while holding their baby during postpartum hospitalization. In this context, newborn babies are at risk for falls and suffocation. The clinical team at one hospital developed a newborn infant safety bundle to promote safe sleep and minimize risk of infant falls and drops. Results are promising in preventing unsafe sleep conditions and newborn falls.